2010
DOI: 10.1093/neuonc/noq004
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase as a novel target for meningioma therapy

Abstract: High levels of fatty acid synthase (FAS) expression have been reported in hormone receptor-positive tumors, including prostate, breast, and ovarian cancers, and its inhibition reduces tumor growth in vitro and in vivo. Similar to other hormone receptor-positive tumor types, meningiomas are progesterone receptor- and estrogen receptor-immunoreactive brain tumors. To define the role of FAS in human meningioma growth control, we first analyzed the FAS expression using a tissue microarray containing 38 meningiomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
(39 reference statements)
1
24
0
4
Order By: Relevance
“…They found that the growth of orthotopic xenografts of malignant mesothelioma cells was strongly inhibited in mice treated with the Fasn inhibitor C75. In addition, Haase et al reported that Fasn expression was elevated in 70% of atypical grade II and anaplastic grade III meningiomas, and that treatment with cerulenin significantly decreased NF2 -null meningioma cell survival in vitro and reduced tumor volumes in xenografts (50). These results, combined with our data in Nf2 -null MEFs and Schwann cells, suggest that changes in lipid synthesis may be a general function in cells lacking Merlin.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the growth of orthotopic xenografts of malignant mesothelioma cells was strongly inhibited in mice treated with the Fasn inhibitor C75. In addition, Haase et al reported that Fasn expression was elevated in 70% of atypical grade II and anaplastic grade III meningiomas, and that treatment with cerulenin significantly decreased NF2 -null meningioma cell survival in vitro and reduced tumor volumes in xenografts (50). These results, combined with our data in Nf2 -null MEFs and Schwann cells, suggest that changes in lipid synthesis may be a general function in cells lacking Merlin.…”
Section: Discussionmentioning
confidence: 99%
“…For Western blotting and real-time PCR, 25 meningiomas of different WHO grades were analyzed. Immunohistochemistry was conducted using a tissue microarray (TMA) as previously described (17). The TMA comprised 53 meningioma samples: 30 tumors were grade I (10 meningothelial, 7 fibroblastic, 7 transitional, 3 angiomatous, 1 microcystic, 2 secretory subtypes), 14 were atypical grade II, and 9 were anaplastic grade III meningiomas according to the recent WHO classification (1).…”
Section: Tumor Materials and Immunohistochemical Studiesmentioning
confidence: 99%
“…FAS inhibitor (cerulein) decreased meningioma cell survival in vitro. Thus, increased FAS expression in human meningiomas represents a novel therapeutic target for the treatment of unresectable or malignant meningiomas (Haase et al 2010 ;Schaller et al 2007Schaller et al , 2008.…”
Section: Resultsmentioning
confidence: 99%